Online banking acceptance in Malaysia: a students' behaviour perspective - Mohd. Israil, Khaliq Ahmad; Khan, Mohd. Imran; Jan, Muhammad Tahir (Malaysian Institute of Management, 2010)
Purpose: Adopting the technology acceptance model, this research examines the factors that determine intention to use online banking in Malaysia, focusing on students of different faculties and different age groups of different higher educational institution in Malaysia. Perceived ease of use and perceived usefulness are considered to be the fundamental factors in detennining the acceptance and use of various information technologies. Design/methodology/ approach - The approach takes the form of an empirical study with 303 usable responses on a questionnaire with five-point Likert scale. Findings - The results indicate that perceived usefulness and perceived ease of use are strong determinants of the students' behavioural intention to adopt online banking in Malaysia. According to descriptive statistics, we have got 70.6% male and 29.4% female's response. Out of which, are generally having 46.5% of their accounts in Bank Muamalat and 32.7% in Bank Islam, and more than 50% of them having current accounts in their respective banks. Usually 88.4% students are in between 15 to 30 years of their age. Most of them were the master's students of different fields and approximately 50% utilise online banking services from the bank. Research limitationsl implications - The use of convenience sampling in this study weakens research bbjectivity and the relatively small size of the sample somewhat limits generalisations. Originality/value - Extends the understanding of the technology acceptance model from students' behaviour perspective.